O DILEMA DE ISHMAEL: UMA ANÁLISE PRAGMÁTICA DE NEVE SOBRE OS CEDROS COM BASE NA TEORIA DA RELEVÂNCIA - Rauen, Fábio José; Silva, Célia Maria da (Intercâmbio, 2010)
This paper analyses the ostensive-inferential processes in scenes of Scott Hicks’ film “Snow on cedars”. The character Ishmael Chambers is focused based on the Sperber and Wilson (1986, 1995), and Carston’s (1988) concepts of logical form, explicature, and implicature.